Proposed treatment algorithm for hallux rigidus - Herrera-Perez, Mario; González-Martín, David; Viladot-Pericé, Ramón (Journal of the Foot & Ankle, 2021)
This study performs a literature review on the treatment of hallux rigidus and proposes a treatment algorithm. This literature systematic review expanded a similar study conducted in 2014 by the authors and analyzed the levels of recommendation according to scientific evidence. Most articles found in the search present scarce evidence (level IV or case series), we only found 8 articles with an at least moderate level of recommendation (B); of these, only one article had a level of evidence I. Conservative treatment is effective with the implementation of footwear modifications, use of insoles, and infiltrations with hyaluronic acid. Cheilectomy, either isolated or combined with Moberg osteotomy, shows good outcomes in stage III, or moderate, although its outcomes worsen after 5 years. Metatarsophalangeal joint (MTPJ) arthrodesis is still the gold standard in stage IV, or advanced. In recent years, the technique of interposition arthroplasty has re-emerged, especially with the use of a synthetic cartilage implant (Cartiva®), with outcomes at least similar to those of MTPJ arthrodesis in comparative studies. Level of Evidence III; Therapeutic Studies; Systematic Review of Level III Studies.